(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To determine the risk factors affecting the results of decompressive craniectomy in patients with traumatic brain injury at Thong Nhat Hospital. Subjects and Methods: A retrospective cross-sectional study of all patients diagnosed with acute subdural hematoma or hemorrhagic cerebral contusion or both with indications for decompressive craniectomy since January 2017 to January 2020 at Thong Nhat Hospital. Results: We collected 172 cases that met the stated conditions and obtained the following results: at the time of discharge, most patients had good outcomes (69.18%), 30, 19% of cases had bad outcomes (GOS 1-2-3). The investigated risk factors affecting the poor outcome included: the amount of newly formed hematoma after surgery >22.68ml (p<0.001), compression of the basal cistern (p<0.05), intraventricular hemorrhage (p<0.05), Rotterdam score on CTscan at admission (p<0.05). Conclusion: Decompressive craniectomy is widely used and saves the lives of many traumatic brain injury patients with intracranial hematoma, but it also brings with it many serious consequences later on. The assessment of clinical and laboratory risk factors helps to choose appropriate treatment and predicts a positive outcome for the patient in the future.